Industrial gas flaring practices - Cheremisinoff, Nicholas P. (Scrivener Publishing ;, 2013)
This volume tackles for the first time in decades the world's gas flaring practices, a difficult, hot-button issue of our time, whose consequences are only just beginning to be understood. The book examines both the technical and environmental aspects of gas flaring, highlights different flare designs, and presents real-world case studies illustrating the proper use of gas flaring and how to avoid polluting flaring events. The only guide of its kind, this remarkable book can help professionals in the oil and gas industry take an important step toward reducing worldwide CO2 emissions.